2019
DOI: 10.3390/insects10070207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet Quality and Temperature on Stable Fly (Diptera: Muscidae) Development

Abstract: The effects of diet quality and temperature on the development time and size of stable flies, Stomoxys calcitrans (L.), was evaluated. Both development time and size varied relative to diet quality and temperature, and their effects were additive. Diet quality and temperature made similar contributions to the variance in size whereas temperature was responsible for >97% of the variance in development time. Regression analysis predicted the shortest development time, egg to adult, to be 12.7 days at 32 °C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…This was due to an earlier study which showed that constant incubation temperatures at 35°C, 20°C and 15°C resulted in high mortalities in immature Stomoxys forms [ 20 ]. For Stomoxys calcitran s, egg to adult survival for all of the constant temperatures was similar to those observed by Florez-Cuadros, Berkebile [ 29 ]. Maintaining an incubation microclimate with a humidity of 70% and a temperature of 27° C provided a large population of Stomoxys spp under laboratory settings, reaching 70% or more of the number of stock pupae available.…”
Section: Discussionsupporting
confidence: 84%
“…This was due to an earlier study which showed that constant incubation temperatures at 35°C, 20°C and 15°C resulted in high mortalities in immature Stomoxys forms [ 20 ]. For Stomoxys calcitran s, egg to adult survival for all of the constant temperatures was similar to those observed by Florez-Cuadros, Berkebile [ 29 ]. Maintaining an incubation microclimate with a humidity of 70% and a temperature of 27° C provided a large population of Stomoxys spp under laboratory settings, reaching 70% or more of the number of stock pupae available.…”
Section: Discussionsupporting
confidence: 84%
“…The conditions of this bioassay provided some of the most important information of the data set obtained from the present study, because, considering the possibility of creating an integrated stable fly control system using EPNs, the temperature that these organisms can withstand is a crucial factor for the success of such an application. These data indicate that IJs of H. baujardi LPP7 are highly vulnerable to both pure vinasse and temperatures close to the limit for stable fly development ( Florez-Cuadros et al, 2019 ), while H. bacteriophora HP88 proved to be little affected. Studies dealing with the heat resistance of the genus Heterorhabditis indicate that, in general, the optimal temperature for the development, infection, and reproduction of these EPNs is around 25 °C ( Shaurub et al, 2015 ).…”
Section: Resultsmentioning
confidence: 85%
“…Next, emergence traps (described below) were placed over the manure pats for 14 days—enough time for horn fly and face fly larvae to develop and be captured as adults. In 2018, the traps were kept in place for an additional 7 days to capture any stable flies, Stomoxys calcitrans (L.) (Diptera: Muscidae), that emerged from the manure pat area (stable fly development is about 21 days at 25C; Florez‐Cuadros et al, 2019). Flies were removed from traps about once per week.…”
Section: Methodsmentioning
confidence: 99%